AlGaN-Based Multiple Quantum Well Deep Ultraviolet Light-Emitting Diodes With Polarization Doping - Jianjun Chang; Dunjun Chen; Junjun Xue; Kexiu Dong; Bin Liu; Hai Lu; Rong Zhang; Youdou Zheng (IEEE Photonics Journal)
The characteristics of AlGaN-based deep-ultraviolet (DUV) light-emitting diodes (LEDs) with polarization-doped p-type layers were numerically analyzed. The energy band diagrams, carrier distributions in the multiple quantum wells (MQWs) and the p-type regions, electroluminescence spectra, current-versus-voltage (I–V) curves, and radiative recombination rates in MQWs, were investigated. The results indicate that DUV LEDs with polarization-doped p-type layers have lower electron leakage, better hole injection efficiency, and higher lighting emission intensity over conventional DUV LEDs. The results also reveal a significant improvement on these characteristics by increasing the Al content of the last quantum barrier in polarization-doped DUV LEDs.